Retroauricular island flap for partial ear reconstruction: case reports - Lauro Arnoldo Ferreira Koehler; Verena Benedick Coimbra; Marcus Vinicius Cunha; Cristiane Camargo Ferreira; Guilherme Vasconcelos Silveira; Camila Garcia Sommer; João Guilherme Cavalcanti Krieger; Antonio Roberto Bozola (Revista Brasileira de Cirurgia Plástica, 2019)
Partial ear defects can be treated in several ways, including primary closure, healing by secondary intention, or flaps. Several surgical options have been described for reconstruction in order to maintain the natural contour of the ear, without sacrificing healthy tissues or changing the aesthetics and function. In this article, we present two cases of reconstruction of chondrocutaneous defects of the ear after resection of basal cell carcinoma in the central region of the ear, with the production of a retroauricular island flap transposed through a cartilaginous window with the de-epidermized pedicle. The donor area healed following a primary closure. This procedure can be performed in a single stage, yields satisfactory aesthetic and functional results, and is safe because the retroauricular region is richly vascularized.